2015
DOI: 10.3390/rel6030988
|View full text |Cite
|
Sign up to set email alerts
|

Ethnography of Religious Instants: Multi-Sited Ethnography and the Idea of “Third Spaces”

Abstract: Attempts to understand contemporary religious practice, and its associated communities and identities, must take into consideration the way that these phenomena exist in both virtual and physical spaces, as well as the way that, in some instances, religion bridges or erases this dichotomy. The approach here focuses on those forms of religious practice that do not fit easily into one or the other type of space. Starting with existing discussions of ethnographic methodologies for studying religious practice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…28 The emphasis on practices requires that the study focus on "real-life human behavior" "to gain a unique understanding of the context and thought that informs such behavior." 29 Thus, archival ethnography is a suitable methodology for a study of the unstated norms and practices of teachers and their relationship to the archival processes undertaken as part of classroom instruction, such as locating primary sources for lesson planning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The emphasis on practices requires that the study focus on "real-life human behavior" "to gain a unique understanding of the context and thought that informs such behavior." 29 Thus, archival ethnography is a suitable methodology for a study of the unstated norms and practices of teachers and their relationship to the archival processes undertaken as part of classroom instruction, such as locating primary sources for lesson planning.…”
Section: Methodsmentioning
confidence: 99%
“…One main participant was a second grade teacher, and two others participated occasionally: a fourth grade teacher and a school librarian. According to Julian Murchison, 30 participant observation can be used to open "avenues to important types of information hard to obtain or access." To obtain implicit experience-based information unique to the education profession and the context of teaching with primary sources, the researcher developed relationships with the teachers and the school librarian over an academic year by regularly participating in the planning of primary source-based student exercises, adhering to classroom norms and schedules, and attending weekly curriculum meetings.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, ethnography has long been established in social science approaches to the study of religion, in research on contemporary religious communities and other forms of religiosity, now also including multi-sited ethnography for the study of the "digital and multisited dimensions of contemporary religious practices" (Murchison and Coats 2015, 989). The study of religious change or "religion in process" with its "fleeting, ephemeral, and impermanent" aspects including digital data especially calls for adapted ethnographic methods (Murchison andCoats 2015, 1001).…”
Section: The Assets Of Ethnography For Studying Changementioning
confidence: 99%
“…Due to the lack of ethnographic teamwork in the digital realm, the examples provided here are not exclusive to this context. The few digital ethnographic projects found that included teamwork did not contain a great amount of detail regarding how the research was undertaken (Fields and Kafai, 2009; Murchison and Coats, 2015).…”
Section: Team Ethnographymentioning
confidence: 99%